BOOK REVIEW Islamophobia and the Politics of Empire:20 Years After 9/11 - Nadhera Mohammad Qasim (University of Darussalam Gontor Press, 2023)
After twenty years of the launching of the global war on terror, Deepa Kumar revised her book Islamophobia and the politics of empire. She incorporated scholarly works in the second edition and provided deeper analysis of imperialist feminism, the political economy of empire and the matrix of anti-Muslim racism. The author concurred that Islamophobia is not a modern anti-racism enterprise, but it has its historical roots in pre-modern era.